Comparative Study of Leaf and Rootstock Aqueous Extracts of Foeniculum vulgare on Chemical Profile and In Vitro Antioxidant and Antihyperglycemic Activities - Karima Sayah; Nasreddine El Omari; Mourad Kharbach; Abdelhakim Bouyahya; Rabie Kamal; Ilias Marmouzi; Yahia Cherrah; My El Abbes Faouzi (Advances in Pharmacological and Pharmaceutical Sciences)
Foeniculum vulgare is a medicinal plant used in Moroccan folk medicine to treat several diseases such as diabetes. The aim of this study was to determine the phenolic bioactive compounds and to evaluate the antioxidant and antihyperglycemic activities of Foeniculum vulgare leaf and rootstock extracts. Phenolic compounds of F. vulgare rootstock and leaf extracts were determined using HPLC-DAD-QTOFMS analysis. The antioxidant activity was evaluated using 1,1-diphenyl-2-picrylhydrazyl (DPPH) and 2,2’-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS•+) radicals. Moreover, the in vitro antihyperglycemic effects were tested by measuring the inhibition of α-amylase and α-glucosidase activities. HPLC-DAD-QTOFMS analysis identified thirty-two phenolic components in both leaf and rootstock extracts. Caffeic acid, quinic acid, and chlorogenic acid were the major compounds of F. vulgare leaf extract (FVLE), while the main compound of F. vulgare rootstock extracts (FVRE) was quinic acid. In the DPPH assay, F. vulgare leaf extract showed important antioxidant activity (IC50 = 12.16 ± 0.02 μg/mL) than F. vulgare rootstock extract (IC50 = 34.36 ± 0.09 μg/mL). Moreover, fennel leaf extracts revealed also the most powerful antioxidant activity (IC50 = 22.95 ± 0.4 μg/mL) in the ABTS assay. The in vitro antihyperglycemic activity showed that F. vulgare rootstock extract exhibited a remarkable inhibitory capacity (IC50 = 194.30 ± 4.8 μg/mL) of α-amylase compared with F. vulgare leaf extract (IC50 = 1026.50 ± 6.5 μg/mL). Furthermore, the inhibition of α-glucosidase was more importantly with F. vulgare rootstock (IC50 of 165.90 ± 1.2 μg/mL) than F. vulgare leaf extracts (203.80 ± 1.3 μg/mL). The funding of this study showed that F. vulgare rootstock and leaf extracts presented several phenolic compounds and showed important antioxidant and antidiabetic effects. We suggest that the identified molecules are responsible for the obtained activities. However, further studies focusing on the isolation and the determination of antioxidant and antidiabetic effects of F. vulgare rootstock and leaf main compounds are required.